2003
DOI: 10.1136/bmj.326.7380.80
|View full text |Cite
|
Sign up to set email alerts
|

Review of deaths related to taking ecstasy, England and Wales, 1997-2000

Abstract: Original article can be found at: http://www.bmj.com/archive/--Copyright BMJ Publishing Group Ltd DOI : 10.1136/bmj.326.7380.8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 2 publications
(2 reference statements)
2
33
0
4
Order By: Relevance
“…In one instance, the possibility of Excited Delirium was recorded. Although the present report comments on only 60 cases, the suicide rates in our other UK studies of stimulant-related fatalities were quantitatively less significant, being in the range of 3-6%: amphetamine-type drugs ; MDMA/ecstasy Schifano et al, 2003b); cocaine (Schifano & Corkery, 2008). The rate for khat-related fatalities was about 31% (sample size = 13) .…”
Section: User Profilementioning
confidence: 82%
“…In one instance, the possibility of Excited Delirium was recorded. Although the present report comments on only 60 cases, the suicide rates in our other UK studies of stimulant-related fatalities were quantitatively less significant, being in the range of 3-6%: amphetamine-type drugs ; MDMA/ecstasy Schifano et al, 2003b); cocaine (Schifano & Corkery, 2008). The rate for khat-related fatalities was about 31% (sample size = 13) .…”
Section: User Profilementioning
confidence: 82%
“…The total figures for each constituent country were added together to obtain UK figures. Different from here, previous UK ecstasy-related fatalities studies (Schifano et al, 2003a;Schifano et al, 2003b) analysed figures collected taking into account the npSAD (Ghodse et al, 2004) definition of ecstasy (MDMA, MDA, MDEA)-related deaths, with coroners' reports at the end of their inquests, and not death certificates, being analysed. Drug-related deaths using the standard definition employed by the Office of National Statistics (Griffiths, 2004) were as follows: ICD-10 codes F11-F16, F18, F19, X40-X44, X60-64, X85 and Y10-Y14.…”
Section: Methodsmentioning
confidence: 99%
“…The risk of 'overdose' with ecstasy has been described in the UK since the early 1990s (Henry et al, 1992). In England and Wales, a steady and constant increase of ecstasy (MDMA, MDA, MDEA)-related fatalities has been observed in the time frame August 1996-April 2002, when a total of 202 related deaths were recorded (Schifano et al, 2003a). A consistent decrease in the purchase costs of ecstasy tablets had been hypothesized, but not demonstrated, to be one of the significant factors for this increase in fatalities (Schifano, 2004).…”
Section: Sage Journal -Jop P R O O F O N L Ymentioning
confidence: 99%
“…Of these drugs, 3,4-methylenedioxymethamphetaime (MDMA, 'ecstasy') is the most popular and has received particular attention because, on rare occasions, its use has led to fatalities (Schifano et al, 2003;Gowing et al, 2002), and because, in animals, it has been shown to have the potential to lead to a persistent loss of brain serotonin (5-HT) axonal markers (Steele et al, 1994;Ricaurte et al, 2000;Green et al, 2003). 'Ecstasy' is normally taken as a pill and in the strictest sense only contains MDMA.…”
Section: Introductionmentioning
confidence: 99%